COMPARISON OF ARTHROCENTESIS PLUS PLATELET RICH PLASMA WITH ARTHROCENTESIS ALONE IN THE TREATMENT OF TEMPOROMANDIBULAR JOINT DYSFUNCTION - Sarwar, Humaira; Shah, Irfan; Khan, Ali Akhtar; Afzal, Muhammad; Babar, Adnan; Baig, Amir Mushtaq (Pakistan Armed Forces Medical Journal, 2021)
Objective: To evaluate the role of combination therapy of platelet rich plasma (PRP) with arthrocentesis and to compare it with arthrocentesis alone in the temporomandibular dysfuction (TMD) patients.Study Design: Quasi experimental study.Place and Duration of Study: Oral and Maxillofacial Surgery department, Armed Forces Institute of Dentistry, Combined Military Hospital Rawalpindi, from Jan 2017 to Jun 2019.Methodology: Forty-two patients diagnosed with refractory unilateral temporomandibular dysfuction, were included in the study. Patients were divided in two groups with 21 temporomandibular joints in each. Arthrocentesis alone was the control group (group I) and arthrocentesis with intra-articular injection of platelet rich plasma (group II) was the study group. Treatment outcomes were assessed and compared for all patients based on clinical parameters of pre and post treatment; for pain, maximal mouth opening and temporomandibular joint clicking sounds.Results: Out of 42 patients, 33 (79%) were females and 9 (21%) were males with mean age of 34.3 ± 8.4 years. There was statistically significant difference in both groups for all variables. The p-value of maximum mouth opening of both groups before and after treatment was 0.746 and 0.01, joint clicking sounds were present in 69% of our patients before the treament and it reduced to 14% after the treatment. There was marked gradual decrease in pain of both groups, group I (6.48 ± 1.470 to 1.81 ± 0.602) and group II (7.29 ± 1.007 to 1.19 ± 0.402).Conclusion: Combination therapy of platelet rich plasma with arthrocentesis is more effective treatment method than.......